EUROCARE-3: survival of cancer patients diagnosed 1990–94—results and commentary - Sant M.; Aareleid T.; Berrino F.; Bielska Lasota M.; Carli P. M.; Faivre J.; Grosclaude P.; Hédelin G.; Matsuda T.; Møller H.; Möller T.; Verdecchia A.; et al. (Annals of Oncology, 2003)
EUROCARE-3 analysed the survival of 1 815584 adult cancer patients diagnosed from 1990 to 1994 in 22 European countries. The results are reported in tables, one per cancer site, coded according to the International Classification of Diseases (ICD)-9 classification. The main findings of the tables are summarised and commented on in this article. For most solid cancers, wide differences in survival between different European populations were found, as also reported by EUROCARE-1 and EUROCARE-2, despite a remarkable (10%) overall increase in cancer survival from 1985 to 1994. Survival was highest in northern Europe (Sweden, Norway, Finland and Iceland), and fairly good in central-southern Europe (France, Switzerland, Austria and Spain). Survival was particularly low in eastern Europe, low in Denmark and the UK, and fairly low in Portugal and Malta. The mix of tumour stage at diagnosis explains much of the survival differences for cancers of the digestive tract, female reproductive system, breast, thyroid, and also skin melanoma. For tumours of the urinary tract and prostate, the differences were explained mainly by differences in diagnostic criteria and procedures. The case mix by anatomic subsite largely explains differences in survival for head and neck cancers. For oesophagus, pancreas, liver and brain cancer, with poor prognoses, survival differences were limited. Tumours, for which highly effective treatments are available, such as testicular cancer, Hodgkin's lymphoma and some haematological malignancies, had fairly uniform survival across Europe. Survival for all tumours combined (an indicator of the overall cancer care performance of a nation's health system) was better in young than old patients, and better in women than men. The affluence of countries influenced overall cancer survival through the availability of adequate diagnostic and treatment procedures, and screening programmes. © 2003 European Society for Medical Oncology.